ADMINISTRATIVE NONJURISDICTIONAL PROCEEDINGS IN THE ACTIVITIES OF CIVIL AVIATION ENTITIES - Lutskyi, Maksym; Husar, Olga (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyse theoretical scientific approaches to the definition of non-jurisdictional proceedings in the system of positive administrative process and to formulate a definition of the concept and types of non-jurisdictional proceedings of civil aviation subjects. Research methods: the study used general and special legal scientific methods, including the method of classifications and groupings, formal - legal, cognitive - analytical. Results: it is established that administrative non-jurisdictional civil aviation proceedings are a demonstration of the public administration authority’s special function of the duty to resolve non-contentious individual groups of cases, aiming to satisfy the rights and freedoms of an individual or a legal person in the field of civil aviation by performing successive actions and stages. Depending on their functional purpose and role in procedural relations, non-jurisdictional proceedings in civil aviation are carried out by entities which can be divided into two groups: 1) subjects of authority; 2) subjects directly involved in aviation activities. The different types of civil aviation proceedings include: rule-making, licensing, attestation, control and supervision, registration, and proceedings related to administration, the conclusion of administrative contracts, and the consideration of proposals and applications from citizens. Discussion: administrative non-jurisdictional civil aviation proceedings are a relatively separate part of the administrative process carried out by civil aviation entities. They are governed by general and special rules of procedural law. The parties to the proceedings have their own procedural status and are not subordinated. They carry out a set of consistent actions to ensure the substantive norms of administrative law; all are conducted on the grounds and within the limits of the normative-legal regulation. Depending on the objectives, administrative non-jurisdictional proceedings in the activities of civil aviation entities are divided into: 1) ensuring that the persons concerned can exercise their subjective rights; 2) ensuring the requirements of the permit and licensing system, obtaining permits (international flight rules); obtaining permits (licences) for economic entities to operate certain activities (permission to use airspace).